2011
DOI: 10.1007/s11340-010-9458-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Lap Joint Fretting Apparatus

Abstract: An experimental apparatus designed specifically for fretting experiments on mechanical lap joints is presented. A piezoactuator is used to impose fretting motion, and a tri-axial load cell is used to measure tangential force as well as possible misalignment forces. A laser nanosensor is employed to measure the relative motion between the joint halves. No post-processing and filtering of the data is needed to obtain the fretting response using this apparatus. Instead, raw data obtained from experiments with mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…For the same value of w / t , an increase in pressure also reduces the energy dissipation. It should be noted that the results reported in this article are in agreement with the experimental finding reported by Eriten et al 19 in terms of both the evolution of the energy dissipation as a function of applied maximum remote load and the effect of bolt pre-load. Although a direct comparison with existing experimental data is outside the scope of the present contribution, it is envisaged that an extension of the approach to incorporate three-dimensional effects will enable performing fast quantitative analyses of energy dissipation in lap joints.…”
Section: Energy Expendituresupporting
confidence: 93%
“…For the same value of w / t , an increase in pressure also reduces the energy dissipation. It should be noted that the results reported in this article are in agreement with the experimental finding reported by Eriten et al 19 in terms of both the evolution of the energy dissipation as a function of applied maximum remote load and the effect of bolt pre-load. Although a direct comparison with existing experimental data is outside the scope of the present contribution, it is envisaged that an extension of the approach to incorporate three-dimensional effects will enable performing fast quantitative analyses of energy dissipation in lap joints.…”
Section: Energy Expendituresupporting
confidence: 93%
“…Comparisons of the identified Iwan model and experimental data are plotted in Figure 12. Parameter χ varies from À0.7 to À0.05, which also agrees with the observations by Ames et al (2009) and Eriten et al (2011aEriten et al ( , 2011b. It is shown that the four-parameter Iwan model can well reproduce joint damping properties with different contact roughness and bolt arrangements.…”
Section: Applications Of Iwan Modelsupporting
confidence: 84%
“…It showed that tangential contact stiffness during micro-slip stage tended to be linear. Initiation of macro-slip was observed at a length scale of 10 À6 m. Hysteresis loops of aluminum and steel joints under different preloads were obtained by Eriten et al (2011aEriten et al ( , 2011bEriten et al ( , 2012 from their quasi-static and dynamic experiments. It is indicated that aluminum joints generally dissipated more energy than steel joints.…”
Section: Introductionmentioning
confidence: 99%
“…Eriten et al [59] obtained the hysteresis curves for a bolted joint by using the apparatus mainly designed for fretting experiments on mechanical lap joints. As shown in Fig.…”
Section: Test Rigs With Directly Applied Tangential Forcementioning
confidence: 99%
“…The apparatus designed by Eriten. Reproduced with permission from Ref [59],. © Society for Experimental Mechanics 2011.…”
mentioning
confidence: 99%